A post hoc analysis utilizing the FDA toxicity grading scale to assess injection site adverse events following immunization with the live attenuated Zoster Vaccine (ZVL) - Zoran Popmihajlov; Lei Pang; Elizabeth Brown; Amita Joshi; Shu-Chih Su; Susan S. Kaplan; English D. Willis (Taylor & Francis Group, 2018)
Background: ZOSTAVAX (ZVL; Zoster Virus Live), is a single dose, live, attenuated vaccine licensed for the prevention of herpes zoster (HZ) and post herpetic neuralgia (PHN) in adults ≥50 years of age. Injection site adverse events (AEs) of erythema, swelling and pain were solicited within 5 days post vaccination in the 2 pivotal studies of ZVL; ZEST (ZOSTAVAX Efficacy and Safety Trial) and SPS (Shingles Prevention Study). Protocol specified criteria were used to report the frequency and intensity of injection site AEs in ZEST and SPS studies. Subsequently, the FDA Toxicity Grading Scale provided guidance for uniform assessment of AEs across all adult vaccine clinical trials. The objective of this post-hoc analysis was to categorize the previously reported injection site AEs in two pivotal trials of ZVL according to the current FDA Toxicity Grading Scale. Methods: The current FDA Toxicity Grading Scale provides a measure for classifying injection site AEs by four grades [Grade 1 (mild); Grade 2 (moderate); Grade 3 (severe) and Grade 4 (life threatening)]. Injection site erythema, swelling, and pain intensity gradings were assigned to the respective FDA Toxicity Grade based on this appropriation. A descriptive analysis of the proportion and risk difference (within 95% confidence intervals) of injection site AEs per the FDA Toxicity Grading Scale is provided. Results: The frequency of injection site AEs (erythema, swelling, pain) after subcutaneous vaccination with ZVL were higher in recipients of ZVL compared with placebo. Majority of the injection site AEs observed were Grade 1 (mild) or Grade 2 (moderate) in intensity. Additionally, Grade 3 (severe) injection site AEs were observed infrequently. Conclusions: Application of the FDA Toxicity Grading Scale provides a uniform AE assessment tool across different adult vaccines. This post hoc summary of injection site AEs using FDA Toxicity Grading Scale provides further evidence of low frequency of severe injection site AEs post ZVL vaccination.